Obsessive–Compulsive Disorder Comorbidity: Clinical Assessment and Therapeutic Implications - Pallanti, Stefano; Grassi, Giacomo; Cantisani, Andrea; Sarrecchia, Elisa; Pellegrini, Matteo (Frontiers in Psychiatry, 2011)
Obsessive–compulsive disorder (OCD) is a neuropsychiatric disorder affecting approximately 1–3% of the population. OCD is probably an etiologically heterogeneous condition. Individuals with OCD frequently have additional psychiatric disorders concomitantly or at some time during their lifetime. Recently, some authors proposed an OCD sub-classification based on comorbidity. An important issue in assessing comorbidity is the fact that the non-response to treatment often involves the presence of comorbid conditions. Non-responsive patients are more likely to meet criteria for comorbid axis I or axis II disorders and the presence of a specific comorbid condition could be a distinguishing feature in OCD, with influence on the treatment adequacy and outcome.